Digital Learning Technology Education for Junior High School Students - Juna Eska; Dinda Djesmedi; M. Syahputra (Universitas Muhammadiyah Jember, 2026)
The rapid development of information technology has encouraged the widespread use of digital information systems among junior high school students. However, the utilization of these technologies is not always accompanied by adequate understanding of responsible, safe, and ethical use. This community service activity aims to improve students’ digital literacy through education on the wise use of digital information systems. The methods employed include counseling sessions, interactive training, and simulations of relevant digital applications. The materials covered include an introduction to digital information systems, digital ethics, personal data security, as well as the positive and negative impacts of digital technology usage. The results of the activity indicate an improvement in students’ understanding of the importance of using digital information systems wisely, as reflected in their increased awareness of data security and responsible technology use. Therefore, this activity is expected to contribute to the development of a generation that is smart, critical, and responsible in utilizing digital technology in the information era